Evaluating the effectiveness of the simple renal cysts treatment using minimally invasive techniques based on the analysis of cyst recurrences - M. V. Varvashenia (Zaporozhye State Medical University, 2015)
Relevance of the work is due the lack of a single uniform opinion concerning the choice of the optimal method of minimally invasive treatment of simple renal cysts. The aim of the research was to assess the effectiveness of minimally invasive treatment of renal cysts by comparative evaluation of percutaneous aspiration with sclerotherapy and drainage and tubeless percutaneous technique to optimize the treatment. Materials and methods. The efficiency of the treatment of cysts according to estimation of the frequency and time of the opening of renal cyst recurrence in 63 patients with simple cyst was studied. Results and Conclusion. It was found that the presence of simple renal cysts (Bosniak category II), regardless of the size of cysts, is an indication to perform sclerotherapy with mandatory drainage of cyst cavity. Also, the findings suggest that in patients with simple kidney cysts (Bosniak category I), with sizes up to 7,99 cm, the method of choice of rational surgical strategy is sclerotherapy without drainage of the cyst cavity.